Systematic evaluation of the impact of stimulation intensity on neuroplastic after‐effects induced by transcranial direct current stimulation. (8th November 2016) - Jamil, Asif; Batsikadze, Giorgi; Kuo, Hsiao‐I.; Labruna, Ludovica; Hasan, Alkomiet; Paulus, Walter; Nitsche, Michael A.
Abstract : Key points: Applications of transcranial direct current stimulation to modulate human neuroplasticity have increased in research and clinical settings. However, the need for longer‐lasting effects, combined with marked inter‐individual variability, necessitates a deeper understanding of the relationship between stimulation parameters and physiological effects. We systematically investigated the full DC intensity range (0.5–2.0 mA) for both anodal and cathodal tDCS in a sham‐controlled repeated measures design, monitoring changes in motor‐cortical excitability via transcranial magnetic stimulation up to 2 h after stimulation. For both tDCS polarities, the excitability after‐effects did not linearly correlate with increasing DC intensity; effects of lower intensities (0.5, 1.0 mA) showed equal, if not greater effects in motor‐cortical excitability. Further, while intra‐individual responses showed good reliability, inter‐individual sensitivity to TMS accounted for a modest percentage of the variance in the early after‐effects of 1.0 mA anodal tDCS, which may be of practical relevance for future optimizations. Abstract: Contemporary non‐invasive neuromodulatory techniques, such as transcranial direct current stimulation (tDCS), have shown promising potential in both restituting impairments in cortical physiology in clinical settings, as well as modulating cognitive abilities in the healthy population. However, neuroplastic after‐effects of tDCS are highly dependent on stimulation parameters, relatively short lasting, and not expectedly uniform between individuals. The present study systematically investigates the full range of current intensity between 0.5 and 2.0 mA on left primary motor cortex (M1) plasticity, as well as the impact of individual‐level covariates on explaining inter‐individual variability. Thirty‐eight healthy subjects were divided into groups of anodal and cathodal tDCS. Five DC intensities (sham, 0.5, 1.0, 1.5 and 2.0 mA) were investigated in separate sessions. Using transcranial magnetic stimulation (TMS), 25 motor‐evoked potentials (MEPs) were recorded before, and 10 time points up to 2 h following 15 min of tDCS. Repeated‐measures ANOVAs indicated a main effect of intensity for both anodal and cathodal tDCS. With anodal tDCS, all active intensities resulted in equivalent facilitatory effects relative to sham while for cathodal tDCS, only 1.0 mA resulted in sustained excitability diminution. An additional experiment conducted to assess intra‐individual variability revealed generally good reliability of 1.0 mA anodal tDCS (ICC(2, 1) = 0.74 over the first 30 min). A post hoc analysis to discern sources of inter‐individual variability confirmed a previous finding in which individual TMS SI1mV (stimulus intensity for 1 mV MEP amplitude) sensitivity correlated negatively with 1.0 mA anodal tDCS effects on excitability. Our study thus provides further insights on the extent of non‐linear intensity‐dependent neuroplastic after‐effects of anodal and cathodal tDCS. Key points: Applications of transcranial direct current stimulation to modulate human neuroplasticity have increased in research and clinical settings. However, the need for longer‐lasting effects, combined with marked inter‐individual variability, necessitates a deeper understanding of the relationship between stimulation parameters and physiological effects. We systematically investigated the full DC intensity range (0.5–2.0 mA) for both anodal and cathodal tDCS in a sham‐controlled repeated measures design, monitoring changes in motor‐cortical excitability via transcranial magnetic stimulation up to 2 h after stimulation. For both tDCS polarities, the excitability after‐effects did not linearly correlate with increasing DC intensity; effects of lower intensities (0.5, 1.0 mA) showed equal, if not greater effects in motor‐cortical excitability. Further, while intra‐individual responses showed good reliability, inter‐individual sensitivity to TMS accounted for a modest percentage of the variance in the early after‐effects of 1.0 mA anodal tDCS, which may be of practical relevance for future optimizations.